Case Study of the Implementation of Modern Fire Safety and Evacuation Technologies at Sant Cugat Station (Barcelona): Active Dynamic Signage System - ADSS/IADSS Active Dynamic Evacuation Signage in Full-scale Trials - Konopski, Przemysław; Ksit, Barbara; Pilch, Roman (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study evaluates the effectiveness of evacuation guidance in large transport facilities based on full-scale trials conducted at Sant Cugat Station in Barcelona. The analysis is grounded in the assumption that, under dynamically worsening fire conditions involving smoke, elevated temperature, and toxic combustion products, occupants tend to rely primarily on the "nearest-exit" heuristic, while conventional static signage has limited operational influence on route-choice behavior.
Keywords: evacuation guidance; dynamic evacuation signage; Active Dynamic Signage System (ADSS); Intelligent Active Dynamic Signage System (IADSS); Voice Alarm System (DSO); building EXODUS